Pengembangan Aplikasi Manajemen Surat berbasis Web memanfaatkan Teknologi Integrasi Protokol IMAP Gmail (Studi Kasus: CV. Mandiri Nusantara) - Rohimatus Sholihah; Bayu Rahayudi; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The letter is a written communication medium to convey information to the intended party, either for individual or organizational purposes. Management of correspondence CV. Mandiri Nusantara is still done manually until now because the letters received and sent have various types and the number is not small as time goes by. If you still use conventional methods, you have a lot of risk of losing mail data, taking up a lot of space, making it difficult to get mail information, as well as correspondence management processes such as archiving, distributing, and making letters. In archiving there are incoming letters that are received directly in the form of physical documents, whereas some companies or agencies still send incoming letters in the form of physical documents to CVs. Mandiri Nusantara and incoming mail from Gmail. With the existing problems, it is necessary to develop a web-based mail management application to help manage correspondence. Between applications and Gmail can be integrated using the IMAP protocol, retrieve email messages every month from Gmail to be displayed on the application as a CV archive. Mandiri Nusantara. Using the Rapid Application Development (RAD) method in development even though it only requires a relatively fast and short time does not reduce product quality, only 60 - 90 days have maximum results. The results of the development of a web-based mail management application utilizing the IMAP Gmail protocol integration technology (Case Study: CV. Mandiri Nusantara) can assist in managing correspondence such as archiving, distributing, and creating letters and makes it easier to find mail information with 100% valid BlackBox testing results. and the test results for User Acceptance Testing (UAT) conducted by 3 examiners consisting of the director, finance, and the main manager of correspondence or administrators have 88% results, that the web-based mail management application has met the needs of users in managing CV correspondence. Mandiri Nusantara.